PENGEMBANGAN ALAT UKUR KESANTUNAN BAHASA INDONESIA DALAM INTERAKSI SOSIAL BERSEMUKA - Zamzani Zamzani (LITERA, 2011)
This study aims to (1) develop an instrument to measure politeness in Indonesian, (2) conduct a small-scale tryout of the instrument, and (3) develop the instrument into a book. The research subjects comprised Indonesian speakers consistingof students, university students, teachers, lecturers, and other speakers classified on the basis educational background, age, sex, geographical location, and ethnic group. The data were collected through FGD, tests, and interviews. The data were analyzed using the qualitative and quantitative descriptive techniques. The findings show that polite speech acts can be classified on the basis of the topics and functions. Formal face-to-face speech acts can be those in teaching and learning, formal meetings, other academic topics, traditional ceremonies, transactions, negotiations,and public services. Degrees and characteristics of politeness are attributable to a variety of factors.